Parotid gland tuberculous abscess - Ahmad F. Bustomi; Melita Sylvyana; Endang Syamsudin; Kiki A. Rizki (DiscoverSys Inc., 2016)
Clinically speaking, parotid gland tuberculosis is a rare case. Its diagnostic values are hard to determine as it has clinical similarities with neoplasms. Mistakes during diagnosis happen quite often thus additional layer of examinations are required to be conducted. An 18-year-old woman was referred from a privately-owned hospital with initial diagnosis of infected parotic sinistra tumor. Physical examination discovered a swelling on her sinistra parotid gland and a lump at the colli sinistra region. Ultrasound scan showed benign hypoechoic areas and cystic regions at the left of submandibular muscle which then expanded towards the neck. Results from the PPD5TU (-), BTA 3X (1X positive) and FNAB pointed out an existing a/r parotid and colli sinistra or Tuberculous abscess. The diagnosis of parotid gland tuberculosis is often established after conducting superficial parotidectomy. During this discussion we will present and elaborate a case of parotid gland tuberculous abscess which was diagnosed with PPD5TU, BTA and FNAB. The patient managed to be cured with OAT distribution and no recurrences were recorded afterward. Parotid gland tuberculous abscess is rarely found in clinics. Tuberculosis examination (including PPD5TU and BTA) and FNAB need to be conducted to prevent unnecessary treatment and medical operations.